Forward Genetic Screens of Human Glycosylation Pathways Using the GlycoGene CRISPR Library. Issue 4 (15th April 2022) - Kelkar, Anju; Groth, Theodore; Neelamegham, Sriram
Abstract: CRISPR‐Cas9‐based forward genetic screens represent a powerful discovery platform to uncover genes regulating specific biological processes. This article describes a method for utilizing a freely available GlycoGene CRISPR library to knock out any gene participating in human glycosylation in arbitrary cell types. The end product is a stable GlycoGene CRISPR knockout cell library, where each cell contains one or more sgRNA and lacks corresponding function. The cell library can be screened using various lectin/antibody reagents. It can also be applied in functional assays to establish glycan structure‐glycogene‐glycopathway relationships. This is a powerful systems glycobiology strategy for dissecting glycosylation pathways and processes. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Scale‐up and NGS validation of the GlycoGene CRISPR plasmid library Basic Protocol 2 : Preparation of a GlycoGene CRISPR lentivirus pool and an isogenic cell line stably expressing Cas9 nuclease Basic Protocol 3 : Preparation of a GlycoGene CRISPR cell library, self‐inactivation of Cas9, and library validation by NGS Basic Protocol 4 : Enrichment of lectin‐binding or non‐binding cells and related multiplex NGS data acquisition Basic Protocol 5 : Bioinformatics pathway analysis